2013
DOI: 10.1371/journal.pone.0066956
|View full text |Cite
|
Sign up to set email alerts
|

Philopatry and Dispersal Patterns in Tiger (Panthera tigris)

Abstract: BackgroundTiger populations are dwindling rapidly making it increasingly difficult to study their dispersal and mating behaviour in the wild, more so tiger being a secretive and solitary carnivore.MethodsWe used non-invasively obtained genetic data to establish the presence of 28 tigers, 22 females and 6 males, within the core area of Pench tiger reserve, Madhya Pradesh. This data was evaluated along with spatial autocorrelation and relatedness analyses to understand patterns of dispersal and philopatry in tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
5
26
0
Order By: Relevance
“…The number of alleles per locus at the polymorphic loci (n = 16) ranged from three to five (average 3.625), the effective number of alleles per locus ranged from 2.000 to 3.447 (average 2.781), and the mean PIC was 0.575 (Table 2). Considering the small number of individuals in our study, we support our results by examining the mean values of H E and H O (0.675 and 0.668, respectively) of the combined panel (n=16), which are comparable with the reported mean values of H E (0.655 to 0.810) and H O (0.650 to 0.7624) in non-invasive genetic studies carried out on the Bengal tiger (Reddy et al, 2012;Gour et al, 2013;Sharma et al, 2013). We established the relatedness among the captive tigers (n = 8) using the combined panel of highly polymorphic loci and estimated the mean value of the relatedness coefficient (R = -0.143), which indicated that the selected tigers were not highly related to each other, as is mostly expected in captive individuals.…”
Section: Resultssupporting
confidence: 88%
“…The number of alleles per locus at the polymorphic loci (n = 16) ranged from three to five (average 3.625), the effective number of alleles per locus ranged from 2.000 to 3.447 (average 2.781), and the mean PIC was 0.575 (Table 2). Considering the small number of individuals in our study, we support our results by examining the mean values of H E and H O (0.675 and 0.668, respectively) of the combined panel (n=16), which are comparable with the reported mean values of H E (0.655 to 0.810) and H O (0.650 to 0.7624) in non-invasive genetic studies carried out on the Bengal tiger (Reddy et al, 2012;Gour et al, 2013;Sharma et al, 2013). We established the relatedness among the captive tigers (n = 8) using the combined panel of highly polymorphic loci and estimated the mean value of the relatedness coefficient (R = -0.143), which indicated that the selected tigers were not highly related to each other, as is mostly expected in captive individuals.…”
Section: Resultssupporting
confidence: 88%
“…A consequence of this female philopatry is the spatial formation of adult female kin‐clusters, a phenomenon evidenced by the strong spatio‐genetic autocorrelation in female–female dyads in both SSGR and PMC. Matrilineal assemblages are typical among large, solitary carnivores, having been observed in brown bears ( Ursus arctos ; Støen et al, ), pumas (Sweanor, Logan, & Hornocker, ), and tigers ( Panthera tigris ; Smith, ; Goodrich et al, ; Gour et al, ). Strategies to deal with the costs of increased resource competition (for food and mates) implicit in this conservative dispersal by females are assumed to have evolved because of the increased inclusive fitness benefits that accrue—the so‐called “resident fitness hypothesis” (Anderson, ; Lambin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moyer et al 2006;Maher 2009;Croteau et al 2010;Innes et al 2012;Gour et al 2013). The correlation between relatedness and spatial distance in Felidae was revealed in the bobcat (Lynx rufus) (Croteau et al 2010) and the tiger (Panthera tigris) (Gour et al 2013), although in both cases this relationship was evident only in females at a short (a few kilometers) range. These results were explainable with the sex-biased dispersal, as females in many mammals are more like- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 ly to be philopatric than males (Shields 1987), which should cause higher relatedness at closer distance between dyads of females and was proved to occur in bobcats (Janečka et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The question of the relatedness and its effects on the spatial organization of a mammal population has already been addressed in a number of species, including carnivores (e.g. Moyer et al 2006;Maher 2009;Croteau et al 2010;Innes et al 2012;Gour et al 2013). The correlation between relatedness and spatial distance in Felidae was revealed in the bobcat (Lynx rufus) (Croteau et al 2010) and the tiger (Panthera tigris) (Gour et al 2013), although in both cases this relationship was evident only in females at a short (a few kilometers) range.…”
Section: Discussionmentioning
confidence: 99%